Erratum: Demin Yu.A., Demina M. Yu., Shabliy V.A., Sergienko A.N. Effect of Cryopreserved Placental Mesenchymal Stromal Cells on Pro-Inflammatory State In Experimental Type 2 Diabetes mellitus. Probl Cryobiol Cryomed 2015; 25(4): 371–378. - Editorial Board, Problems of Cryobiology and Cryomedicine (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(1):100.